COMMUNITY PARTICIPATION IN WASTE MANAGEMENT IN PINRANG REGENCY: TOWARDS A WASTE-FREE ENVIRONMENT - AR, Andi Bau Inggit; Ruslan, Achmad; Annisa, Arini Nur; Arifin, Arnita Pratiwi; Lestari, Arini Enar; AR, Andi Bau Medlin; Imanullah, Andi Muhammad Aqil; Kadarudin; Rifai, Andi Tenri Famauri; Rastiawaty (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The problem of waste management in Penrang Village is caused by the fact that many people are not yet aware of disposing of waste in its place, the lack of community participation due to the lack of understanding and legal awareness of the community in protecting the environment, the suboptimal management of waste by the local government through TPS3R, and the lack of community understanding regarding Pinrang Regency Regulation no. 7 of 2013 concerning Waste Management. Legal socialization is the best solution that can be offered, so the method of implementing the activities used in lectures and discussions between the PPMU-PK-M Team of Hasanuddin University with the village apparatus and the surrounding community. The community's lack of understanding and awareness regarding their role in waste management causes many problems related to environmental management, especially concerning waste management in Penrang Village. The number of cleaning staff in Penrang Village is also inadequate, so they are overwhelmed in carrying out their duties. The lack of officers hampers the distribution of household waste to the final disposal site. This is because many people refuse to pay their waste transportation fees, even though the fees are managed to become the wages of cleaning staff in the village. In this case, the local government should be able to resolve the issue of wages for cleaning staff in order to achieve good waste management in Penrang Subdistrict.